2017
DOI: 10.3892/or.2017.5797
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 inhibitor induces KG-1a cell differentiation and apoptosis via Akt/NF-κB signaling

Abstract: Heat-shock protein 90 (Hsp 90) acts as a molecular chaperone that maintains protein stability and regulates cell proliferation, survival, differentiation and apoptosis. The present study investigated the effect of Hsp90 inhibition on human acute myeloid leukemia (AML) cells using the novel small-molecule inhibitor SNX-2112. We found that SNX-2112 more potently inhibited KG-1a cell growth than the classical Hsp90 inhibitor 17-(2-dimethylaminoethyl)amino‑17-demethoxygeldanamycin as determined by CCK-8 assay. Flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…HSP90AB1, also recognized as HSP90 beta, is a member of the HSP90 family which includes HSP90 alpha (HSP90AA1) and HSP90 beta. HSP90 proteins play an important role in cell regulation, forming complexes with various transcription factors, cellular kinases, and some molecules [30][31][32]. In this study, we have discovered the effect of the interaction between HSP90AB1 and the CC domain on Bcr-Abl cytoplasm localization and its function in chronic myeloid leukemia cells.…”
Section: Introductionmentioning
confidence: 89%
“…HSP90AB1, also recognized as HSP90 beta, is a member of the HSP90 family which includes HSP90 alpha (HSP90AA1) and HSP90 beta. HSP90 proteins play an important role in cell regulation, forming complexes with various transcription factors, cellular kinases, and some molecules [30][31][32]. In this study, we have discovered the effect of the interaction between HSP90AB1 and the CC domain on Bcr-Abl cytoplasm localization and its function in chronic myeloid leukemia cells.…”
Section: Introductionmentioning
confidence: 89%
“…SNX-2112 was synthesized as previously described in our lab with >98.0% purity [42], dissolved in dimethyl sulfoxide (DMSO) to obtain a 100 mM stock solution, and stored at −20°C. TRAIL was purchased from Merck Millipore (Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Sato et al [46] reported that Akt forms a complex with HSP90, and that inhibition of Akt-HSP90 binding leads to dephosphorylation and inactivation of Akt. It was further reported that inhibition of HSP90 induces differentiation in myeloid cells, and that low concentrations of an HSP90 inhibitor, SNX-2112, arrest cells in the G2/M phase and induce their differentiation and apoptosis, possibly by suppressing Akt and inhibitor of κB kinase, a component of the nuclear factor-κB signaling pathway [47].…”
Section: Hsp90 Inhibitorsmentioning
confidence: 99%